1990
DOI: 10.1111/j.1365-2141.1990.tb07874.x
|View full text |Cite
|
Sign up to set email alerts
|

Surface expression of CD 11b/CD18 of pseudo‐Pelger granulocytes in chronic myeloid leukaemia

Abstract: The aim of the present study was to evaluate the surface membrane glycoproteins of pseudo-Pelger granulocytes in six patients suffering from chronic myeloid leukaemia (CML). We studied the functional and immunochemical activities of five monoclonal antibodies (MoAb) minimally reactive with integrin familial antigens of pseudo-Pelger granulocytes. The study conducted with cytofluorimetric and immunological alkaline phosphatase anti-alkaline phosphatase (APAAP) analysis showed a decreased expression of CD11b/CD1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1993
1993
2000
2000

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Various authors have reported defects in locomotion, chemotaxis. However, little attention has been paid to the possible link between membrane phenotype and granulocyte functional disorders (Watson et al, 1988;Mazzone et al, 1990). 1977;Gahmberget al 1979: Rep0 et al 1979: Ruutu et al, 1981Martin et al, 1983: Boogaerts et al, 1983Mazzone et aI.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Various authors have reported defects in locomotion, chemotaxis. However, little attention has been paid to the possible link between membrane phenotype and granulocyte functional disorders (Watson et al, 1988;Mazzone et al, 1990). 1977;Gahmberget al 1979: Rep0 et al 1979: Ruutu et al, 1981Martin et al, 1983: Boogaerts et al, 1983Mazzone et aI.…”
mentioning
confidence: 99%
“…Preliminary studies have suggested that neutrophil membrane antigens are abnormal in MDS with the persistence of immature myeloid antigens (Martinet al, 1983;Ricevuti et al, 1988;Watson et al, 1988: Rosmarin et al 1989Mazzone et al, 1991). However, little attention has been paid to the possible link between membrane phenotype and granulocyte functional disorders (Watson et al, 1988;Mazzone et al, 1990). Certain PMN surface glycoproteins are thought to be involved in chemotaxis and are absent in certain patients with a history of recurrent infections and impaired neutrophil function (Fearon, 1980; adherence and locomotion in vitro, and diapedesis and migration into inflammatory sites in vivo (Sanchez-Madrid et al, 1983;Harlan et al, 1985: Ross et al, 1985Lanier et al, 1985: Marlin et al, 1986Wallis et al, 1986;Miller et al, 1986: Harlan et al, 1987: Arnaout, 1990.…”
mentioning
confidence: 99%